Westphal Variant of Huntington's Disease - Cote-Orozco, J. E.; Cabarcas-Castro, L.; Ramón-Gómez, J. L.; Zarante-Bahamón, A. M.; Bernal-Pacheco, O.; Espinosa-García, E. (Journal of Pediatric Neurology, 2019)
A Westphal variant of Huntington's disease (HD) is an infrequent presentation of this inherited neurodegenerative disorder. Here, we describe a 14-year-old girl who developed symptoms at the age of 7, with molecular evidence of abnormally expanded Cytosine-Adenine-Guanine (CAG) repeats in exon 1 of the Huntingtin gene. We briefly review the classical features of this variant highlighting the importance of suspecting HD in a child with parkinsonism and a family history of movement disorder or dementia.
Keywords: juvenile Huntington's disease; HTT gene; CAG repeat expansion